KUALITAS PELAYANAN DALAM JASA TRANSPORTASI PUBLIK BUS RAPID TRANSIT (BRT) KOTA SEMARANG - Prayoga, Thoriq Adi; Subowo, Ari; Lituhayu, Dyah (Journal of Public Policy and Management Review, 2015)
The high use of private vehicles and public transportation causing congestion on most roads in the city of Semarang . To reduce the congestion Semarang city government provide an alternative solution , namely policy Trans Bus Rapid ( BRT ) . However , in practice there are few facilities of BRT are not running optimally .